Assessment of Analytical Instrumentation for Boron Measurement in BNCT System - Isman Mulyadi Triatmoko; Sutjipto Sutjipto (Indonesian Journal of Physics and Nuclear Applications, 2017)
The methods boron measurement in BNCT system has generally progressed with developments in analytical instrumentation. Spectrophotometric methods remained the methods of choice for most routine applications until the development of ICP-OES. ICP-OES was also not adequately sensitive for nutritional and medical research involving animal tissues that are naturally low in boron (B). The development of plasma-source MS (e.g., ICP-MS) not only has overcome most of these drawbacks, but also its capability of measuring B isotopes. The application of nuclear reaction methods (mainly prompt-γ spectrometry) has remained limited to some specialized fields. The validity and comparability of three different analytical techniques (QNCR, PGAA, and ICP-MS) for boron measurement in biological samples and application of these methods for examination of blood and tissue samples from a clinical study on boron uptake in blood, tissue, and neoplastic tissue, after infusion of BPA. The PET-based approach to TPS has been applied in BDTPS and a preliminary evaluation of the correct operation has been performed using a heterogeneous boron phantom, called HEBOM. The validation has been accompanied by calculations done with SERA, following the standard approach. BDTPS needs further in vivo experimental validations.